Islam as power: Shi'i revivalism in the oeuvre of Muhammad Husayn Fadlallah - Speidl, Bianka (Routledge studies in Middle Eastern democratisation and government, 2021)
Introduction -- 1. The importance of Muḥammad Ḥusayn Faḍlallāh in Shīʻī Revivalism -- 2. Defining Power as a System and an Intermediate Goal -- 3. Faḍlallāh's Theology of Power -- 4. Spiritual Power as the Engine of Revolution -- 5. Social Power -- 6. Political Power -- 7. Ethics of Power -- 8. Rhetoric of Power -- Conclusion -- Bibliography.